Interleukin-17 In Juvenile Idiopathic Arthritis (Texas Journal of Medical Science, 2023)
Joint diseases of childhood are an actual problem of pediatrics. Juvenile idiopathic arthritis (JIA) is a common chronic systemic inflammatory joint disease in children, the etiological factors of which remain not fully known. The disease can affect children of any age, it is characterized by a long progressive course, leading to the development of contractures and functional insufficiency, and thus the disability of children